Analisis Persepsi Wajib Pajak Orang Pribadi Di Mentawai Mengenai Penggelapan Pajak - Sabailaket, Ani Susanti (CV. SINAR HOWUHOWU, 2024)
This study analyzes the perceptions of individual taxpayers in the Mentawai Islands District regarding tax evasion, a critical issue in the context of tax revenue in Indonesia. The research aims to understand the factors influencing these perceptions, including tax fairness, tax knowledge, tax penalties, subjective norms, and religiosity. A quantitative method was employed using a survey approach among taxpayers who have reported taxes for at least the past two years. Multiple regression analysis results indicate that tax fairness, tax knowledge, and tax penalties significantly influence perceptions of tax evasion, while subjective norms and religiosity also contribute significantly